DIGITAL MARKETING IMPLEMENTATION TRAINING: PRODUCT PHOTOS, PACKAGING DESIGN, AND CONTENT DESIGN AS AN EFFORT TO OPTIMIZE PRODUCT VALUE - Sophia, Elsha; Fadhlillah, Hanif; Sukma, Alifian; Rohmawati, Siti Nur (Universitas Airlangga, 2025)
In an increasingly competitive digital era, micro, small, and medium enterprises (MSMEs) face challenges in marketing their products effectively due to limited digital understanding, lack of visual design skills, and low quality product photos. This problem has a direct impact on the competitiveness and selling value of MSME products, especially within the 'Aisyiyah Surabaya Branch Leadership. To overcome this, digital marketing implementation training was carried out which included product photography techniques, packaging design, and content creation using simple devices such as smartphones and the Canva application. The training method is carried out in several stages: delivery of educational materials, direct practice with mentoring, and post-activity evaluation through the collection of participants' work and focus group discussions (FGD). This training was attended by 32 MSME participants and was held at MI Muhammadiyah 27, Surabaya. The results of the activity showed an improvement, namely as many as 85% of participants understood the concept of digital marketing, 75% produced product photos that are worthy of publication, 70% were able to design attractive packaging, and 65% succeeded in creating content that increases customer interaction. Despite obstacles such as limited devices and time, this training has proven to be effective in improving MSME digital marketing skills and encouraging product value optimization in the digital market. In the future, advanced training is recommended to include aspects of financial management and access to sharia financing as support for business sustainability.